Optimizing State-Owned Enterprises Land Assets using HBU and Value-Based Decision - Susanto, Ifan; Utomo, Christiono (IPTEK Journal of Proceedings Series, 2019)
Competitive business climate, lack of capital and urban land function changes have an impact on land assets that are not optimally used. State-owned land with an area of 32,495 m2 with a market value of 227,773,000,000 rupiah contained a cultural heritage building. The land is located in the east Kalimantan corridor, trade zone and service, which is the waterfront city development area of the city of Surabaya. This study aims to optimize assets and find the best development alternatives in asset utilization to become a profit center for the company. Based on surveys and interviews, found that the possible development alternatives to be carried out were Mixed Use Commercial (a1), Diesel Engine Industry (a2) and Maximize Workshop capacity (a3). Highest and Best Use (HBU) was found to be one of the techniques of decision making in the development of land and property. HBU criteria are used to build a value-based decision hierarchy. Analytical Hierarchy Process (AHP) is applied to develop decision making processes based on preferences and the best choices. The best alternative is obtained from the Satisficing Option calculation. This result is obtained by comparing functions to costs. The function is obtained from the HBU criteria and costs come from the estimated initial costs and life cycle costs (Life Cycle Cost). Based on financial analysis calculation obtained that mixed-use commercial development has the highest and best use Net Present Value (NPV) IDR 2,470,771,622,513 with an investment cost of IDR 1,367,230,380,324. Internal Rate of Return (IRR) is 20.66% with a payback period of 6.70 years. Based on AHP analysis with HBU-Value Based Decision criteria and Satisficing Option calculations it was found that the mixed-use commercial property development is a development alternative chosen by stakeholders to optimize BUMN assets